Accumulation of Capital, Impediment to Efficient Economic System Equilibria - Reuben Soto, Sergio (2023)
This paper is a review of five articles published at the Revista de Ciencias Económicas of the Universidad de Costa Rica, which presents the results of a research program that began with an attempt to explain the crisis of subprime with a heterodox perspective of the economy, using the main categories of Political Economy.  The articles cover a span of 12 years from the first published in this journal in 2008, to the last, published in this same journal in 2020.  To present an empirical basis that would give solidity to the hypotheses and inferences formulated in these articles, a study is added with data on the business composition of four economic sectors in Costa Rica. The paper’s aim is to articulate the central hypotheses proposed and supported in the reviewed articles, in order to facilitate their knowledge. And secondly, to present a study with empirical data of the main productive sectors of Costa Rica, which give objective support to the proposed hypotheses. Despite the methodological limitations of the empirical study, the work suggests a trend in the concentration of productive capital accumulation, which is consistent with the proposed hypotheses. The conclusions of the theoretical research and the result of the empirical study rises issues to support the need to regulate in multiple ways, according to the conditions of each society, the process of capital accumulation that governs nationals’ productions.